2002
DOI: 10.1124/dmd.30.6.709
|View full text |Cite
|
Sign up to set email alerts
|

The Licorice Root Derived Isoflavan Glabridin Inhibits the Activities of Human Cytochrome P450S 3A4, 2B6, and 2C9

Abstract: ABSTRACT:The potent antioxidants licorice root extract and glabridin, an isoflavan purified from licorice root extract, were tested for their ability to modulate the activities of several cytochrome P450 (P450) enzymes. P450 3A4, the major human drug metabolizing P450 enzyme, was inactivated by licorice root extract and by glabridin in a time-and concentration-dependent manner. The inactivation was NADPH-dependent and was not reversible by extensive dialysis. Further analysis showed that the loss in enzymatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(83 citation statements)
references
References 32 publications
2
81
0
Order By: Relevance
“…Different classes of licorice compounds showed distinct activities on P450 isozymes. Flavonoid glycosides (3-7), saponins (10,15,16,19), and phenolic acids (1,2) showed weak regulatory activities, with inhibition or activation rates of less than 35% at 10 Ī¼M. Most of their IC 50 values were higher than 200 Ī¼M.…”
Section: P450 Inhibition Assay For 40 Licorice Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different classes of licorice compounds showed distinct activities on P450 isozymes. Flavonoid glycosides (3-7), saponins (10,15,16,19), and phenolic acids (1,2) showed weak regulatory activities, with inhibition or activation rates of less than 35% at 10 Ī¼M. Most of their IC 50 values were higher than 200 Ī¼M.…”
Section: P450 Inhibition Assay For 40 Licorice Compoundsmentioning
confidence: 99%
“…Previous reports have revealed that glycyrrhetinic acid could inactive CYP 2E1 (14), glabridin (form Glycyrrhiza glabra) could inhibit the activities of 3A4, 2B6, and 2C9 (15), and that glycyrrhizic acid could induce (16) or inhibit (17) human CYP 3A4. Unfortunately, results from single compounds could not represent the action of licorice, which is a multicomponent mixture containing more than 400 compounds (18).…”
Section: Introductionmentioning
confidence: 99%
“…One patient exhibited digoxin toxicity due to hypokalemia induced by licorice intake [Harada et al 2002]. Licorice root extracts not including glycyrrhizin causes inhibition of P450 and cytochrome P450 3A4 (CYP3A4) systems [Tsukamoto et al 2005;Kent et al 2002]. A study demonstrated the potentiation of warfarin effects due to the inhibitory effect of licorice on the hepatic microsomal enzyme system [Heck et al 2000].…”
Section: Licorice-related Complicationsmentioning
confidence: 99%
“…In particular, bioactivation, or the metabolic activation of a compound to an electrophilic reactive intermediate, which subsequently undergoes covalent binding to critical cellular macromolecules and interferes with their www.intechopen.com function, has long-standing recognition as a biochemical mechanism of organ toxicity (Miller & Miller 1947;Mitchell et al, 1973;Masubuchi et al, 2007). Several examples exist of natural products undergoing P450-mediated bioactivation and irreversible P450 enzyme inhibition and hepatotoxicity (Johnson et al, 2003;Zhou et al, 2004;Surh & Lee 1995;He et al, 1998;Kent et al, 2002). Furthermore, natural products are known to result in significant interactions with coadministered therapeutic agents resulting in adverse effects or therapeutic failures (Dietz & Bolton 2007;Yuan et al, 2004;Kupiec & Raj 2005).…”
Section: Cytochrome P450-mediated Formation Of Reactive Metabolitesmentioning
confidence: 99%